Occurrence and human health risk assessment of antibiotics in cultured fish from 19 provinces in China - Tang, Yunyu; Lou, Xiaoyi; Yang, Guangxin; Tian, Liangliang; Wang, Yuan; Huang, Xuanyun (Frontiers in Cellular and Infection Microbiology, 2022)
The occurrence of antibiotics and potential health risk of 300 cultured fish samples from 19 provinces in China were investigated. The levels of 28 antibiotics (15 fluoroquinolones, 4 tetracyclines, 8 macrolides and rifampin) in 8 fish species were measured through liquid chromatography electrospray tandem mass spectrometry. As a result, 10 antibiotics were detected with an overall detection frequency of 24.3%, and the individual detection frequency of antibiotics ranged from 0.33 to 16.7%. The extremely high concentrations (above 100 µg/kg) of doxycycline and erythromycin were found in the samples. Antibiotics with high detection frequency was noticed in largemouth bass (41.2%), followed by snakehead (34.4%) and bream (31.2%). Specifically, Heilongjiang, Xinjiang, Qinghai and Gansu presented high detection frequency values of more than 60%. Moreover, the highest mean concentration was observed in Shandong, and the concentration covered from 34.8 µg/kg to 410 µg/kg. Despite the high detection frequency and levels of antibiotics were found in samples, ingestion of cultured fish was not significantly related to human health risks in China, according to the calculated estimated daily intakes and hazard quotients. These results provided us the actual levels of antibiotics in cultured fish and human health risk assessment of consuming fishery products.